The good side of inflammation: Staphylococcus aureus proteins SpA and Sbi contribute to proper abscess formation and wound healing during skin and soft tissue infections - Gonzalez, Cintia Daniela (2019)
Staphylococcus aureus is the most prominent cause of skin and soft tissue infections (SSTI) worldwide. Mortality associated with invasive SSTI is a major threat to public health considering the incidence of antibiotic resistant isolates in particular methicillin resistant S. aureus both in the hospital (HA-MRSA) and in the community (CA-MRSA). To overcome the increasing difficulties in the clinical management of SSTI due to MRSA, new prophylactic and therapeutic approaches are urgently needed and a preventive vaccine would be welcome. The rational design of an anti-S. aureus vaccine requires a deep knowledge of the role that the different bacterial virulence factors play according to the type of infection. In the present study, using a set of isogenic deficient mutants and their complemented strains we determined that the staphylococcal surface proteins SpA and Sbi play an important role in the induction of inflammatory cytokines and chemokines in the skin during SSTI. SpA and Sbi initiate signaling cascades that lead to the early recruitment of neutrophils, modulate their lifespan in the skin milieu and contribute to proper abscess formation and bacterial eradication. Moreover, the expression of SpA and Sbi appear critical for skin repair and wound healing. Thus, these results indicate that SpA and Sbi can promote immune responses in the skin that are beneficial for the host and therefore, should not be neutralized with vaccine formulations designed to prevent SSTI.